Implementasi Etika Bisnis Islam Agen HPAI dalam Transaksi Jual Beli Produk Herbal Penawar Al Wahida Indonesia - Rahmawati, Rahmawati (UIR Press, 2019)
This research is conducted to find out the implementation of Islamic business ethic of HPAI agents in trading at PT Herbal Penawar Alwahida Indonesia Tuanku Tambusai Tampan Subdistrict Pekanbaru. Then, method used in this research is qualitative description with data collection technique using questionnaires and documentation. The sample of this research is permanent agents consist of 83 agents using purposive sampling technique. The result shows that the parmanent agents which have become the members of HPAI at PT Herbal Penawar Alwahida Indonesia Tuanku Tambusai Tampan Subdistrict Pekanbaru have conducted Islamic business ethic really well in trading which can be seen from ethic code and service standard settled.